The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.dark.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

How to obtain a cosmological constant from small exotic R4

Abstract: In this paper we determine the cosmological constant as a topological invariant by applying certain techniques from low dimensional differential topology. We work with a small exotic R 4 which is embedded into the standard R 4 . Any exotic R 4 is a Riemannian smooth manifold with necessary non-vanishing curvature tensor. To determine the invariant part of such curvature we deal with a canonical construction of R 4 where it appears as a part of the complex surface K3#CP (2). Such R 4 's admit hyperbolic geometr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 48 publications
1
33
0
Order By: Relevance
“…Another interesting result in this direction is [1]. In their paper the authors show how the cosmological constant may arise from a topological quantity via Chern-Simons invariants.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Another interesting result in this direction is [1]. In their paper the authors show how the cosmological constant may arise from a topological quantity via Chern-Simons invariants.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…This simple idea opens the door to explicit calculations. In case of the transition S 3 → ∂A = Σ(2, 5, 7), the corresponding results can be found in [39]. If one assumes a Planck-size (L P ) 3-sphere at the Big Bang, then the scale a of Σ(2, 5, 7) changes like a = L P · exp 3 2 · CS(Σ(2, 5, 7)) with the Chern-Simons invariant CS(Σ(2, 5, 7)) = 9 4 · (2 · 5 · 7) = 9 280 and the Planck scale of order 10 −34 m changes to 10 −15 m. Obviously, this transition has an exponential or inflationary behavior.…”
Section: Reconstructing a Spacetime: The Ksurface And Particle Physicsmentioning
confidence: 93%
“…The embedding of the Akbulut cork is essential for the following results. In [39], it was shown that the embedded cork admits a hyperbolic geometry if the underlying K3 surface has an exotic smoothness structure. This simple property has far-reaching consequences.…”
Section: Reconstructing a Spacetime: The Ksurface And Particle Physicsmentioning
confidence: 99%
See 1 more Smart Citation
“…By general arguments (see [15,16]) the complement C(K + ) admits a hyperbolic structure, i.e. it is a homogenous space of constant negative curvature.…”
Section: Small Exotic Rmentioning
confidence: 99%